1980
DOI: 10.1111/j.1365-2478.1980.tb01259.x
|View full text |Cite
|
Sign up to set email alerts
|

Model Studies on Some Aspects of Resistivity and Membrane Polarization Behaviour Over a Layered Earth*

Abstract: Electrolytic model tank experiments to study resistivity and time domain induced polarization (IP) response over layered earth models were initiated primarily to facilitate the understanding of field results. Alternate layers of clay and sand (or clay‐coated sand) with, in some cases, a surficial layer of water were assembled in the tank and resistivity and IP measurements made for a range of electrode spacings using the Wenner configuration. Graphite and silver‐silver chloride electrodes were used as current … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

1981
1981
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…The resistivity and MT data were inverted individually. Whereas IP data have been inverted simultaneously with resistivity data, doing so reduces ambiguity significantly (Roy and Elliot ; Olorunfemi ). Furthermore, DC resistivity data are a byproduct without any additional further cost of IP survey.…”
Section: Simulated Examplesmentioning
confidence: 99%
See 1 more Smart Citation
“…The resistivity and MT data were inverted individually. Whereas IP data have been inverted simultaneously with resistivity data, doing so reduces ambiguity significantly (Roy and Elliot ; Olorunfemi ). Furthermore, DC resistivity data are a byproduct without any additional further cost of IP survey.…”
Section: Simulated Examplesmentioning
confidence: 99%
“…The field data of apparent resistivity (Figure (a)) and apparent chargeability (Figure (a)) analysed here have been adapted from Roy and Elliot (). Both apparent resistivity and apparent chargeability were acquired for hydrogeological studies in the Chatham area of New Brunswick, Canada, using Schlumberger array.…”
Section: Simulated Examplesmentioning
confidence: 99%
“…Vacquier et al (1957) [1] and Marshall and Madden (1959) [2] described, respectively, the time domain IP measurements on artificial clay and sand mixtures and a theoretical model for membrane (clay) polarization. Ogilvy and Kuzmina (1972) [11] described additional time domain measurements on artificial mixtures, while Roy and Elliot (1980) [12] used horizontal layers of varying clay-sand composition to model negative apparent chargeabilities due to geometric effects. Vanhala and Soininen (1995) [13] carried out laboratory measurements using spectral IP on soil samples in order to assess the effect of mineralogy, grain size distribution, moisture content, and electrolyte composition on the resistivity of soil material.…”
Section: Introductionmentioning
confidence: 99%
“…Many workers have indicated that by interpreting IP sounding (IPS) data together with DC resistivity measurements, the ambiguity in interpretation is significantly reduced. IPS curves often offer better resolution in delineating a layered structure than that of resistivity alone (Roy and Elliot 1980;Olorunfemi 1985). Note that the IP observables such as chargeability, frequency effect and phase are equivalent (Hohmann 1990).…”
Section: Introductionmentioning
confidence: 99%